The effectivity of heat conduction in the sterilization of long-handled dental instruments - Ong, Katherine C.; Yu, Jennifer H.; Ramos Jr., Aurelio B. (Adviser).
This study is conducted with the objective to determine whether or not heat conduction is effective in the sterilization of long handled dental instruments, which method is effective and the time it takes to sterilize the instruments for the different media. its concluded that heat conduction is an effective method in sterilizing long handled instruments. The use of glass as the conducting medium with at least 10 minutes immersion is the most effective method, followed by sand and salt with a minimum of 15 minutes immersion.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.